R&D Rivalry with Licensing or Imitation - Katz, Michael L.; Shapiro, Carl (American Economic Review, 1987)
The authors study the rivalry between two firms to develop an innovation in a dynamic setting that allows for post-development dissemination of the innovation, such as licensing or imitation. This dissemination may cause the noninnovating firm to benefit from the discovery. When this occurs, conventional results in the economics of R&D no longer need apply They find that industry leaders will tend to develop minor innovations, but will develop major innovations only if imitation is difficult. Copyright 1987 by American Economic Association.